Exploring the short-run implications of the COVID-19 pandemic on affordability in the Irish private rental market - Conor O'Toole; Rachel Slaymaker; Kieran McQuinn; Cathal Coffey; Eoin Corrigan (The Economic and Social Research Institute (ESRI), 2020)
The COVID-19 pandemic represents the most severe and rapid shock to the Irish economy in modern times. This paper examines the short-run, three-month impact of the pandemic on rental affordability and missed payments for a specific cohort of the private rental sector in Ireland. It focuses on those households which, at the outset of the pandemic, were not in receipt of state rental supports such as the Housing Assistance Payment (HAP) or Rent Supplement (or paying a local authority rent). These households were deemed the most at risk of affordability challenges due to the high level of rents they were paying. In this report we classify such households as non-supported private renters. Unless otherwise stated, any reference to 'households' refers to this group.
Keywords: 330; Coronavirus; Mietwohnung; Miete; Irland